The impact of the Trade-Related Aspects of Intellectual Property Rights (TRIPS) on the right to health and the right to development: a study of the implementation of TRIPS in Zimbabwe - Munemo, Ropafadzo Blessing (University of KwaZulu-Natal, 2021)
The right to health and the right to development are intertwined socio-economic rights that affect the well being and growth of a country’s populace. Most developing and least developed countries face challenges in ensuring access to essential medicines vis a vis the realisation of the right to health and full potential of development. Patents, provided for under the TRIPS Agreement are partly to blame for the lack of access to essential medicines as they account for the excessive pricing of medicines. Zimbabwe being a developing country currently facing dire economic and political challenges but being obliged under the International and Regional Human Rights Conventions it subscribed to, has to ensure the progressive realisation of the right to health and development. However, as a member of the TRIPS Agreement, there are limitations to the country’s ability to ensure access to medicines and healthcare for developmental purposes. This thesis has outlined the problematic provisions of the TRIPS Agreement and Zimbabwe’s attempt to use the flexibilities provided to its advantage. Zimbabwe has only put into use the flexibility of compulsory licensing and parallel importation to a limited extent; hence the recommendation that even though the country has domesticated the Agreement to its advantage, the country needs to explore other flexibilities comprehensively and promote the realisation of the rights to health and development.
Keywords: Access to medicine; Health care costs; Intellectual property; Public health; TRIPs; Trade tariffs; Zimbabwe

The Interface Between Competition Law and Intellectual Property Law in Kenya - Jerobon, Rotich Caroline (University of Nairobi, 2016)
The interaction between competition law and intellectual property law has often attracted divergent views from scholars and practitioners of each respective sphere of law. Whereas some argue that the two are in conflict with each other and cannot be reconciled. The aforementioned tension between competition law and intellectual property law has been traced to the objectives of each. On the one hand, intellectual property rights confer upon their owners an exclusive right to behave in a particular way while on the other hand competition law strives to keep markets open. Other scholars have argued that, in real sense and practice, the two are actually not in conflict but rather that they complement each other. The question then becomes, is there really an irreconcilable difference between the two areas of law? This paper seeks to establish how the two aspects of law interact and seeks to propose that there be created a balance to alleviate the perceived conflict between the two. This paper will identify the areas in which the balance can be struck. It will also seek to establish how the Kenyan legislative framework as well as the courts has dealt with the conflict. It will proceed from understanding the goals and objective of both intellectual property law and competition law. This will provide the backdrop against which the alleged conflict originates from. A comparative study with other developed jurisdictions will be undertaken so as to advise on the route that should be taken by Kenya on the interface and a conclusion drawn on how the two areas relate and recommendations drawn from the issues identified in the study made.
Keywords: Competencia; Competition law; Intellectual property

Designing justice: a critical analysis of intellectual property rights within the fashion industry - Parbhoo, Sade (University of KwaZulu-Natal, 2016)
Designers are those individuals within our society with a desire and drive to create. In general designers can be found in all facets of industry and good designers (and ultimately good designs) are the very backbone upon a successful business is built. Designers are required to marry practical knowledge with artistic ability and we are reliant on their skills and to turn abstract ideas into formal designs for everything from the groceries we purchase, the cars we drive and of course, the clothes we wear. Whilst there is no definitive delineation of what a fashion design is, generally fashion designs relate to the creation of designs that focus on clothing, apparel and accessories. The style and functionality of the end products rest firmly within particular time frames, economic and socio-cultural environments within which particular designers find themselves. Accordingly the fashion design industry is never one that stagnates but rather is one that is constantly evolving. In South Africa, the fashion industry is blossoming. As an emerging economy, it is important to create opportunities and not barriers for entry into particular sectors for emerging entrepreneurs. The entire fabric of the fashion industry has certainly changed over time and these changes have brought an increased focus on issues of copying and counterfeiting. It is the contention of some in the industry that there is a need for stricter protection of the actual design in and of itself. Using intellectual property rights as a means of protecting fashion designs is very fitting as every new design begins with an idea, which then evolves, though a process of creative engagement and application of skill and labour to become the final original end product. Designers seeking to protect their designs would need to consider the provisions of the Copyright Act, the Designs Act and the Trade Marks Act. These Acts may in some instances provide a means for protect the actual design incidentally, i.e. by protecting the designer‟s rights in relation to reputation and goodwill associated with the goods whilst in others may afford protection to the design itself. The focus of this research will be a discussion of the legal mechanisms available to fashion designers in South Africa for the protection of their designs using their intellectual property rights and an assessment of whether the fashion industry is in need a stronger intellectual property regime than the current one.
Keywords: Design protection; Fashion industry; Intellectual property; Ownership; Retail trade; South Africa

Users' entitlements under the fair dealing exceptions to copyright - Shay, Richard Michael (Stellenbosch University, 2012)
This thesis analyses current South African copyright law to ascertain the proper interpretation and application of the fair dealing provisions contained in the Copyright Act 98 of 1978. Copyright law ensures that authors’ works are not used without their consent, which they can grant subject to compensation or conditions attached to the use. Fair dealing exceptions allow the general public to use copyright works for certain purposes without the copyright owner’s consent and without paying compensation. These provisions are intended to balance copyright owners’ interests with the interest that members of the public have in using copyright works for socially beneficial purposes. These provisions typically allow the use of a copyright work for the purposes of research or private study, personal or private use, criticism and review, and news reporting. Unfortunately there is no South African case law concerning the fair dealing provisions, and the application of these exceptions remains unclear. This study aims to clarify the extent of application of the fair dealing exceptions to copyright infringement so that courts may be more willing to consider foreign and international law and in doing so develop South African intellectual property law. The social and economic policy considerations underlying the fair dealing exceptions are considered to determine their function. International conventions relating to copyright and neighbouring rights are examined, specifically the provisions allowing exceptions to copyright. The legislation and case law of Australia and the United Kingdom are analysed to determine the proper interpretation and application of these statutory defences. This knowledge is then used to inform South African law. The Copyright Act 98 of 1978 does not contain a fair dealing exception for parody and satire. Australian legislation does contain such an exception, and it is analysed in that context. An exception for parody is proposed for South African law, and the need for and application of this provision is considered. The constitutionality of the proposed exception is evaluated in terms of its impact on the constitutional property rights of copyright owners.
Keywords: Australia; Copyright law; Fair dealing; Fair use; Great Britain; Intellectual property; South Africa; Trademarks

Explaining Copyright: The Normative Implications of its Sociotechnical Construction - Nicholson, Scott (Queen’s University, 2008)
The construction of copyright law can be causally explained by two possible types of explanation: dialectical explanations and material explanations. I argue that an adequate causal description of the copyright discourses of Western legal systems must incorporate a material explanation in order to account for many of the general and particular characteristics of the evolution of copyright. As a vast variety of contingent and interactive social and technical conditions have caused the evolution of copyright, we should expect a plausible material explanation to be multifaceted and multi-layered. However, in addition to providing a causal sociohistorical description, a good legal explanation should also seek to include a normative account detailing the moral grounds of the law, or lack thereof. Dialectical explanations can be teleological: they can presuppose that the law is directed towards a perfect legal state and that it is essentially guided by a set of moral ideals. Material explanations, on the other hand, are essentially non-normative and do not explicitly address moral questions. But this does not entail the elimination of moral considerations from material explanations. As I aim to show, we should not address the moral and sociohistorical elements of copyright legal discourses independently because they are causally connected: moral justifications have been rhetorically used by social actors to influence lawmaking processes, and conversely, changes in technical conditions have given rise to sociotechnical formations that enable and structure the norms of copyright. Given this, I propose that lawmakers should adjudicate and legislate from a broad and flexible standpoint. They should not attempt to merely apply old principles to new problems, but should comprehend new moral norms introduced by new conditions, and balance them against the older, more established principles enshrined in traditional intellectual property theories.
QSpace: Queen's Scholarship & Digital Collections
Keywords: Copyright; Intellectual property